The Concept of Society in the Perspective of Islamic Education Philosophy - Rifai, Ahmad Zulyan; Tufani, Ahmad; Yani, Ahmad; Mulyadi, Akrom; Jaenullah, Jaenullah (Assyfa Journal of Multidisciplinary Education, 2024)
The concept of society within the framework of Islamic education philosophy is founded on principles of equality, compassion, and justice. This study seeks to explore how Islamic pedagogical principles shape societal values, highlighting the interplay between individual responsibilities and communal harmony. By examining case studies of diverse Muslim communities, we aim to uncover variations in the application of these principles and address challenges in balancing traditional teachings with contemporary societal needs. The research utilizes qualitative methods, including interviews and content analysis, to provide a nuanced understanding of the dynamic relationship between Islamic education and societal development. The findings reveal that while Islamic educational philosophy promotes unity and social justice, practical implementation requires adapting to local cultural contexts and overcoming socio-political barriers. This abstract outlines the importance of continual dialogue and adaptation in fostering an inclusive and progressive Islamic society. Such efforts are critical for promoting global understanding and cooperation within diverse communities. Ultimately, the study calls for an integrated approach that respects both traditional Islamic values and modern societal demands, ensuring that the ideals of brotherhood, equality, and justice remain at the core of educational and societal practices.